Development of a Responsive Portfolio Website and Online Ordering System for CV Putra Pahala Tua - Yoputra, Keaton; Suwarno (Program Sarjana Sistem Informasi, Universitas Internasional Batam, 2024)
The importance of a portfolio website cannot be ignored, especially for micro, small, and medium enterprises (MSMEs) who want to increase their business visibility and credibility. Therefore, this website development project is expected to provide MSMEs like CV Putra Pahala Tua an effective tool to compete in an increasingly digitized market. The entire portfolio website and its complementary systems (online ordering system and admin panel) development process uses the Scrum framework guided by Agile principles. The website was developed using the PHP programming language with the CodeIgniter framework. The features developed included: home page, news page, catalog page, login page, as well as an online ordering system for customers to make order requests and an admin panel for company employees to manage front-page content and order requests from customers. Once developed, the website went through black box testing, and was ultimately deployed on the internet through shared hosting, before being handed over to the MSME for management. The website was rated positively by the MSME and is expected to help in enhancing its reputation and provide sustaining benefits.